2003
DOI: 10.1063/1.1610237
|View full text |Cite
|
Sign up to set email alerts
|

Embeddings in space–times sourced by scalar fields

Abstract: The extension of the Campbell-Magaard embedding theorem to general relativity with minimally-coupled scalar fields is formulated and proven. The result is applied to the case of a self-interacting scalar field for which new embeddings are found, and to Brans-Dicke theory. The relationship between Campbell-Magaard theorem and the general relativity Cauchy and initial value problems is outlined.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 59 publications
(83 reference statements)
2
36
0
Order By: Relevance
“…This is because due to the presence of the BD scalar field the ambient space is not, in general, Ricci-flat. However, it can be shown that a new geometrical frame for 5D Brans-Dicke theory exists and is supported by an extension of the Campbell-Magaard theorem [14]. On the other hand, as in the case of the induced-matter approach, the theory provides no way of obtaining a unique spacetime from a given 5D metric, and that would require further mathematical conditions on the embedding, or a kind of new dynamical principle to select the possible choices of physically plausible spacetimes [32].…”
Section: Final Remarksmentioning
confidence: 97%
See 1 more Smart Citation
“…This is because due to the presence of the BD scalar field the ambient space is not, in general, Ricci-flat. However, it can be shown that a new geometrical frame for 5D Brans-Dicke theory exists and is supported by an extension of the Campbell-Magaard theorem [14]. On the other hand, as in the case of the induced-matter approach, the theory provides no way of obtaining a unique spacetime from a given 5D metric, and that would require further mathematical conditions on the embedding, or a kind of new dynamical principle to select the possible choices of physically plausible spacetimes [32].…”
Section: Final Remarksmentioning
confidence: 97%
“…The anwer to this question was provided by the Campbell-Magaard theorem, which asserts that any analytic n-dimensional Riemannian space can be locally embedded in a (n + 1)-dimensional Ricci-flat space [8][9][10][11]. The rediscovery of Campbell-Magaard theorem by physicists and its connection with modern spacetime embedding theories gave rise to a series of new results and extensions in the cases when the ambient space: (a) is an Einstein space [12], (b) has a non-degenerate Ricci-tensor [13], (c) is sourced by scalar-fields [14]. The latter case includes embeddings in spaces that are solutions of the vacuum Brans-Dicke (BD) field equations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in these proposals our ordinary spacetime is viewed as a hypersurface embedded in a five-dimensional (5D) manifold (the bulk). On the other hand, mathematical theorems regulate these embeddings, in particular, the Campbell-Magaard theorem [13,14] and its extensions specify the conditions under which the embeddings are possible [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Since the nineteenth century, isometric embeddings into higher dimensions have been explored extensively in geometry [1][2][3][4][5][6][7], with more focus on non-Euclidean spaces in recent times. Theorems given by Dahia and Romero [5,6] prove that there exists a local isometric embedding of any analytic pseudo-Riemannian manifold into an Einstein space and also into a more general pseudo-Riemannian space.…”
Section: Introductionmentioning
confidence: 99%